Oxidative Stress Mediates the Disruption of Airway Epithelial Tight Junctions through a TRPM2-PLCγ1-PKCα Signaling Pathway - Xu, Rui (Molecular Diversity Preservation International (MDPI), 2013)
Oxidative stress has been implicated as an important contributing factor in the pathogenesis of several pulmonary inflammatory diseases. Previous studies have indicated a relationship between oxidative stress and the attenuation of epithelial tight junctions (TJs). In Human Bronchial Epithelial-16 cells (16HBE), we demonstrated the degradation of zonula occludens-1 (ZO-1), and claudin-2 exhibited a great dependence on the activation of the transient receptor potential melastatin (TRPM) 2 channel, phospholipase Cγ1 (PLCγ1) and the protein kinase Cα (PKCα) signaling cascade.